A Prospective Cohort Study To Estimate The Amount Of Scarring Of Liver In Non-Alcoholic Fatty Liver Disease In Type 2 Diabetes Patients. - Puttagunta, Madhurima; A, Raveesha; . K, Prabhavathi; . K, Prabhavathi (Journal of Neonatal Surgery, 2025)
Background: NAFLD encompasses a variety of disorders, including non-alcoholic fatty liver, non-alcoholic steatohepatitis (NASH), fibrosis, and cirrhosis. The FIB-4 index is primarily used to detect liver fibrosis in alcoholic and infectious liver disease patients. This study will aid in identifying people at risk of developing liver fibrosis in non-alcoholic fatty liver disease patients using the FIB-4 score. Material and methods: A prospective study was undertaken among 31 patients with Nonalcoholic fatty liver disease. All patients were treated to a full clinical examination, including laboratory tests. All cases were subjected to CBC, RFT, and LFT investigations. Fibroscan and LSM were conducted according to manufacturer instructions. Results: In this study, the mean BMI was 28.0, AST was 137.5, ALT was 74.0, platelet count was 166548.4, and HbA1c was 8.3. Approximately 64.5% of the cases had F4 grade fibrosis. The correlation coefficient between HbA1c and FIB-4 score was -0.135, which was negative but not significant. Conclusion: It is critical that diabetics be checked for, recognized, and referred for advanced fibrosis in a proactive way.